2014
DOI: 10.4028/www.scientific.net/amm.501-504.510
|View full text |Cite
|
Sign up to set email alerts
|

Investigate on Axial Load Behaviors of T-Shaped CFT Stub Columns with Binding Bars

Abstract: . Abstract. Tests on TCFT-WB, including 11 specimens with binding bars and 5 without binding bars under axial compression were carried out. The effects of parameters on the behavior of specimens such as failure mode, bearing capacity and ductility are analyzed to provide experimental data for the following research. The formula to calculate ultimate strength of TCFT-WB columns under axial compression are deduced from the constitutive relationship of TCFT-WB. The calculated results are compared with those calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…(3) When Steel box section is welded open, and Inner and outer side are convenient for welding, saves labor and material, weld quality can be guaranteed easily. At present, this binding bars of steel pipe concrete members, from the research literature at home and abroad, which is only studied by some scholars in South China University of Technology and Tongji University ,who studied the theoretical and experimental axial compression and bias force performance [5][6][7][8], But did not study excessive flexural performance of bending member on binding bars, The results confirmed the binding bars larger to improve and enhance the mechanical properties of the concrete filled steel tube. Therefore, Studying this constructor of binding bars ,which used in flexural performance of flexural members is very meaningful, This also is a useful extension for studying the concrete-filled steel tube by the theory of bending and steel-concrete composite beams.…”
Section: Introductionmentioning
confidence: 99%
“…(3) When Steel box section is welded open, and Inner and outer side are convenient for welding, saves labor and material, weld quality can be guaranteed easily. At present, this binding bars of steel pipe concrete members, from the research literature at home and abroad, which is only studied by some scholars in South China University of Technology and Tongji University ,who studied the theoretical and experimental axial compression and bias force performance [5][6][7][8], But did not study excessive flexural performance of bending member on binding bars, The results confirmed the binding bars larger to improve and enhance the mechanical properties of the concrete filled steel tube. Therefore, Studying this constructor of binding bars ,which used in flexural performance of flexural members is very meaningful, This also is a useful extension for studying the concrete-filled steel tube by the theory of bending and steel-concrete composite beams.…”
Section: Introductionmentioning
confidence: 99%